Septic Shock and Spontaneous Gangrenous Gas Necrosis of the Spleen Secondary to Clostridium perfringens: The Importance of Source Control. (6th May 2021) - Oskutis, Morgan; Reaven, Matthew
Abstract : Clostridium perfringens is a rare cause of septic shock, occurring most frequently in immunocompromised patients. An uncommon cause of Clostridium perfringen septicemia is spontaneous gangrenous gas necrosis of the spleen, where the primary treatment is splenectomy. We present a case of septic shock caused by spontaneous gangrenous gas necrosis of the spleen secondary to Clostridium perfringens in a patient whose profound pancytopenia made obtaining definitive source control extremely difficult.